Modified nano titanium dioxide, PE (polyethylene) film as well as preparation method and application of modified nano titanium dioxide and PE film

Through the adjustment of the mesoporous structure of modified nanotitanium dioxide, the problem of discomfort in the degradation rate of PE films is solved, and the effect of protecting the pipes during the storage period and rapidly degrading after the period is achieved, maintaining excellent mechanical properties.

CN119708629AInactive Publication Date: 2025-03-28MAOMING LIANSU BUILDING MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411992018.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The degradation rate of existing PE films is too fast or too slow, unable to degrade effectively on their own, and insufficient mechanical properties, resulting in environmental pollution and waste of resources.

Method used

By using modified nanotitanium dioxide, mesoporous silica formed by a silicon source is coated with nanotitanium dioxide, controlling its pore size and specific surface area, thereby adjusting the degradation rate of PE films.

Benefits of technology

It realizes that PE films effectively protect the pipes during the storage period, and can quickly degrade after the storage period, maintain excellent mechanical properties, and meet the needs of environmental protection and resource utilization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005223846290000101
    Figure BDA0005223846290000101
  • Figure BDA0005223846290000111
    Figure BDA0005223846290000111
Patent Text Reader

Abstract

The invention belongs to the technical field of PE thin film production, and particularly relates to modified nano titanium dioxide, a PE thin film and a preparation method and application of the modified nano titanium dioxide and the PE thin film. According to the invention, the modified nano titanium dioxide is obtained by adding the hexadecyl trimethyl ammonium bromide and the n-octylamine. And then, combining with low-density polyethylene, a filler, a light screening agent, a nucleating agent, an anti-blocking agent and other materials to prepare the PE film. Wherein the modified nano titanium dioxide has a relatively small aperture, so that the contact area between the modified nano titanium dioxide and organic matters is reduced, and the degradation rate of the film is further reduced; the light shielding agent carbon black not only can absorb and reflect ultraviolet rays, but also can quench free radicals on the surface of the nano titanium dioxide, so as to synergistically weaken the photocatalytic degradation effect; meanwhile, the nucleating agent effectively solves the problem that the physical properties of the film are reduced due to the addition of the light screening agent. The synergistic effect of the raw materials ensures that the PE film can effectively protect the pipe within the storage period, and meanwhile, the PE film can be quickly degraded after the storage period and keeps excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of PE film production, and more specifically, relates to a modified nano titanium dioxide, a PE film, and a preparation method and application thereof. Background Art

[0002] Polyethylene film (PE film) is the main packaging material for plastic pipes. It provides good protection for the appearance of the pipes before they are used, effectively avoiding damage caused by transportation and storage. However, once the plastic pipes are put into use, if the PE film is discarded at will, the thermoplastic resin polyethylene, which is polymerized from ethylene monomers, is difficult to degrade in the natural environment due to its stable molecular structure, which undoubtedly aggravates the severity of environmental problems. In recent years, with the widespread application of plastic pipes in many fields such as construction, agriculture, and municipal administration, the environmental pollution caused by their appearance packaging materials has become increasingly prominent.

[0003] Currently, there are significant challenges in the degradation performance of PE films: on the one hand, the degradation rate of some PE films is too fast (such as the weight loss rate of PE films within one year is greater than 20%), and they have even become brittle during the one-year storage period before the pipes leave the factory, and cannot effectively complete their task of protecting the appearance of the pipes; on the other hand, the degradation rate of some PE films is extremely slow (such as the weight loss rate of PE films within one and a half years is less than 40%), and even within a year or even longer, they still cannot effectively degrade on their own. At the same time, their mechanical properties are insufficient (such as elongation at break <400%) to provide sufficient anti-fracture ability, which not only causes a waste of resources, but also poses a long-term potential threat to the natural environment. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of the existing PE film, such as the degradation rate of the existing PE film is too fast (the weight loss rate of the PE film within one year is greater than 20%) or the degradation rate is too slow (the weight loss rate of the PE film within one and a half years is less than 40%), the inability to effectively degrade by itself and the insufficient mechanical properties (such as the elongation at break is less than 400%), and to provide a modified nano titanium dioxide.

[0005] Another object of the present invention is to provide a method for preparing the modified nano titanium dioxide.

[0006] Another object of the present invention is to provide a PE film.

[0007] Another object of the present invention is to provide a method for preparing the above PE film.

[0008] Another object of the present invention is to provide the use of the modified nano titanium dioxide or the PE film in the preparation of tube packaging.

[0009] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0010] The invention protects a modified nano titanium dioxide, which comprises the following raw materials: nano titanium dioxide, hexadecyltrimethylammonium bromide (CTAB), n-octylamine, and a silicon source;

[0011] Wherein, the molar ratio of CTAB to n-octylamine is 1:(1.8-2.2).

[0012] The modified nano-titanium dioxide of the present invention is prepared by coating mesoporous silica formed by a silicon source. This coating structure has significant advantages: it can not only effectively prevent the agglomeration of nano-titanium dioxide, thereby maintaining a good catalytic degradation effect; but also, by adjusting the molar ratio of CTAB and n-octylamine, the pore size of the mesoporous silica can be accurately controlled. As the pore size decreases, the specific surface area of ​​the modified nano-titanium dioxide in contact with organic matter also decreases accordingly, thereby achieving accurate control of the degradation rate of surface adsorbed organic matter by nano-titanium dioxide.

[0013] Furthermore, the preparation method of the mesoporous silica comprises the following steps: hexadecyltrimethylammonium bromide and nitric acid form a worm-like micelle system, and n-octylamine is added as a co-surfactant under acidic conditions to prepare synthetic mesoporous silica.

[0014] Furthermore, the nano titanium dioxide is anatase nano titanium dioxide and / or rutile nano titanium dioxide.

[0015] Furthermore, the silicon source includes one or more of tetraethyl orthosilicate, silicate, and silane.

[0016] Furthermore, the molar ratio of hexadecyltrimethylammonium bromide to n-octylamine is 1:(1.8-2.2). The selection of this ratio range is crucial: if it is lower than this range, the degradation rate of the PE film will be accelerated, and it will not meet the storage period (one year) requirement of the tube packaging; if it is higher than this range, the degradation rate of the PE film will be significantly slowed down, posing a potential threat to the friendliness of the natural environment. Therefore, by strictly controlling this molar ratio, the controllability and environmental friendliness of the PE film in terms of degradation rate are ensured.

[0017] The present invention provides a method for preparing the modified nano titanium dioxide, comprising the following steps:

[0018] S1. The hexadecyl trimethyl ammonium bromide and n-octylamine were thoroughly mixed to obtain a transparent solution;

[0019] S2. Add a silicon source to the transparent solution obtained in step S1, adjust the pH to 9 to 11, mix thoroughly, add the nano-titanium dioxide dispersion, heat to 40 to 50 ° C, react fully, and post-treat to obtain a precursor;

[0020] S3. The precursor obtained in step S2 is heated to 500-600° C. and calcined to obtain modified nano titanium dioxide.

[0021] Under acidic conditions, CTAB forms positively charged micelles, which further aggregate to form worm-like structures due to the hydrophobic and electrostatic interactions between CTAB molecules in the solution. Subsequently, n-octylamine is added to the system as a cosurfactant, which interacts with CTAB to further stabilize and optimize the micelle structure. Next, the silicon source undergoes hydrolysis and polymerization around the micelles, gradually forming a silica skeleton. At this time, by adding nano-titanium dioxide to the system, the nano-titanium dioxide will interact with the silica skeleton being formed and be wrapped in the mesoporous structure of silica. After calcination to remove the CTAB template molecules, a nano-titanium dioxide material modified with silica of a mesoporous structure is obtained. Among them, when the ratio of CTAB to n-octylamine increases, n-octylamine will be more inclined to interact with silicates, resulting in a tighter arrangement of silicates around the micelles. This tight arrangement limits the formation of mesopores, resulting in a reduction in the pore size of mesoporous silica.

[0022] Furthermore, in step S2, the method for preparing the nano titanium dioxide dispersion comprises the following steps:

[0023] The nano-titanium dioxide is fully dispersed in the solvent to obtain a nano-titanium dioxide dispersion.

[0024] Furthermore, the dispersion is ultrasonic dispersion.

[0025] Furthermore, the solvent is water and / or ethanol.

[0026] Furthermore, in step S2, the sufficient reaction is performed by stirring and hydrolyzing at a shear rate of 300 to 400 r / min for 12 to 24 hours.

[0027] Furthermore, in step S2, the post-treatment includes centrifugation, washing, and drying.

[0028] Furthermore, the centrifugation is to centrifuge the solution after the reaction to separate the product and collect the precipitate.

[0029] Furthermore, the washing is to use ethanol to wash the collected precipitated product 3 to 5 times.

[0030] Furthermore, the drying is to dry the washed product at room temperature.

[0031] Specifically, in step S2, the post-treatment includes centrifuging the solution after the reaction to separate the product, collecting the precipitate, washing the collected precipitate product with ethanol for 3 to 5 times, and drying the washed product at room temperature.

[0032] Furthermore, in step S3, the calcination time is 5 to 7 hours.

[0033] The present invention protects a PE film, which comprises the following components by weight:

[0034] 60-80 parts of linear low-density polyethylene;

[0035] 20-40 parts of metallocene linear low density polyethylene;

[0036] 5-10 parts of filler;

[0037] 3-5 parts of the above modified nano titanium dioxide;

[0038] 1-3 parts of carbon black;

[0039] 1 to 3 parts of opening agent;

[0040] Nucleating agent 0.5 to 1 part.

[0041] This application successfully prepared a PE film by combining linear low-density polyethylene, metallocene linear low-density polyethylene, fillers, opening agents and other raw materials, and utilizing the synergistic effect of modified nano titanium dioxide, light shielding agent carbon black, and nucleating agent. The film can not only undergo catalytic degradation under natural light conditions, but also its degradation rate can be adjusted by modified nano titanium dioxide to meet the different storage cycle requirements of pipe packaging. Specifically, the combination of linear low-density polyethylene and metallocene linear low-density polyethylene effectively improves the heat sealing performance of PE film; the appropriate addition of fillers plays a role in reducing costs and increasing efficiency, and improves the physical and chemical properties and processing properties of PE film; modified nano titanium dioxide has a smaller mesoporous pore size, which effectively reduces the specific surface area in contact with organic matter, thereby significantly slowing down the catalytic degradation process and prolonging the degradation time of the film; the addition of light shielding agent carbon black significantly enhances the film's ability to absorb and reflect ultraviolet rays, effectively reducing the damage of ultraviolet rays to the film material, and further weakening the photocatalytic degradation effect of modified nano titanium dioxide. In addition, carbon black can also quench excited substances (hydroxyl radicals, etc.) produced by nano-titanium dioxide under ultraviolet irradiation, especially by transferring hydrogen atoms to these highly oxidizing excited substances, preventing them from undergoing photo-oxidation reactions with organic matter adsorbed on the surface of nano-titanium dioxide; at the same time, the introduction of nucleating agents effectively compensates for the problem of decreased physical properties of the film caused by the addition of light shielding agent carbon black, ensuring that the film maintains good degradation performance while maintaining stable overall physical properties; finally, the addition of opening agents effectively reduces the direct contact area between films, thereby achieving a reduction in the friction coefficient of the film surface, making the film easier to open, and preventing the adhesion effect when the film is attached. The synergistic effect of the above raw materials ensures that the PE film can effectively protect the pipe during the storage period, and can quickly degrade after the storage period, while maintaining excellent mechanical properties.

[0042] Furthermore, the linear low-density polyethylene includes one or more of polyethylene 7042, polyethylene 7050, and polyethylene 9047.

[0043] Furthermore, the metallocene linear low-density polyethylene includes one or more of polyethylene D139, polyethylene 5220G, and polyethylene AT6101.

[0044] Furthermore, the combination of linear low-density polyethylene and metallocene linear low-density polyethylene is beneficial to improving the heat-sealing properties of the film.

[0045] Furthermore, the filler is polyethylene filler masterbatch and / or talcum powder.

[0046] Furthermore, the opening agent includes one or more of silicon dioxide, oleamide, and erucic acid amide. It can be evenly dispersed inside the film, and build a large number of fine and solid convex structures on the surface of the film. These structures effectively reduce the direct contact area between the films, thereby reducing the friction coefficient of the film surface, making the film easier to open. At the same time, the presence of these convex structures also promotes the smooth penetration of external air between the two layers of film, effectively preventing the formation of a vacuum state when the two layers of film are attached, thereby preventing the film from sticking.

[0047] Furthermore, the nucleating agent includes one or more of sodium benzoate, 1,3:2,4-di-p-methylbenzylidene sorbitol, and benzoic acid.

[0048] Preferably, the nucleating agent is sodium benzoate. Sodium benzoate can more effectively improve the crystallinity of the PE film and reduce the transparency reduction phenomenon caused by adding carbon black, thereby enhancing the overall physical properties of the PE film.

[0049] The method for preparing the PE film of the present invention comprises the following steps:

[0050] All raw materials are fully mixed according to proportion, heated to 160-175°C, extruded, and post-treated to obtain PE film.

[0051] The preparation method of the PE film is not only simple in conditions and convenient in operation, but also has significant advantages such as easy availability of raw materials, stable process, environmental protection and energy saving.

[0052] Furthermore, the post-processing includes blowing, pulling, cooling and winding.

[0053] Furthermore, the blowing is to blow up the material by compressed air to increase the transverse strength of the film and make the film thickness uniform.

[0054] Furthermore, the traction is to pull and stretch the film while inflating, so as to increase the longitudinal strength of the film.

[0055] Furthermore, the cooling is to use cold air to blow the outer surface of the film to cool the film bubble and fix it.

[0056] Furthermore, the winding is to arrange the PE film into a roll to facilitate subsequent processing and use.

[0057] Specifically, the post-processing includes blowing the material with compressed air to increase the transverse strength of the film and make the film thickness uniform. While blowing, the film is stretched to increase the longitudinal strength of the film. Cold air is blown on the outer surface of the film to cool the film bubble and shape it. The PE film is arranged into a roll for subsequent processing and use.

[0058] The present invention protects the application of the modified nano titanium dioxide or the PE film in the field of pipe packaging.

[0059] Compared with the prior art, the present invention has the following beneficial effects:

[0060] The present invention obtains modified nano titanium dioxide by adding hexadecyltrimethylammonium bromide and n-octylamine. Subsequently, it is combined with low-density polyethylene, fillers, light shielding agents, nucleating agents, opening agents and other materials to prepare a PE film. Among them, the smaller pore size of the modified nano titanium dioxide reduces its contact area with organic matter, thereby reducing the degradation rate of the film; the light shielding agent carbon black can not only absorb and reflect ultraviolet rays, but also quench free radicals on the surface of nano titanium dioxide, synergistically weakening the photocatalytic degradation effect; at the same time, the nucleating agent effectively compensates for the problem of decreased physical properties of the film caused by the addition of the light shielding agent. The synergistic effect of the above raw materials ensures that the PE film can effectively protect the pipe during the storage period, and can be quickly degraded after the storage period, and maintains excellent mechanical properties. DETAILED DESCRIPTION

[0061] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0062] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0063] Linear low-density polyethylene: Polyethylene 7042 was purchased from Sinopec;

[0064] Metallocene linear low-density polyethylene: Polyethylene D139 was purchased from ExxonMobil;

[0065] Light shielding agent: Carbon black / titanium dioxide were purchased from Longxing Chemical Co., Ltd. and China National Nuclear Huayuan Titanium Dioxide Co., Ltd., respectively;

[0066] UV absorber: UV-531 Jiangsu Minglin Chemical Technology Co., Ltd.;

[0067] Antiblocking agent: erucamide DY-014 was purchased from Dongguan Dayue Plastic Technology Co., Ltd.;

[0068] Nucleating agent: Sodium benzoate was purchased from Shanghai Dongda Chemical Co., Ltd.;

[0069] Filler: Polyethylene filler masterbatch TC-313T was purchased from Shanghai Yinshun Technology Co., Ltd.

[0070] Example 1 Preparation of a modified nano-titanium dioxide and PE film

[0071] 1. Preparation of modified nano-titanium dioxide

[0072] S1. Disperse 5 g of nano titanium dioxide powder in 200 mL of water solvent, and then disperse it fully using ultrasound to obtain a nano titanium dioxide dispersion;

[0073] S2, dissolving 1.25 g of hexadecyltrimethylammonium bromide (CTAB) in 100 mL of water, and stirring to obtain a template solution; then, adding 2.50 g of n-octylamine to the solution so that the mass ratio of CTAB to n-octylamine is 1:2, and finally obtaining a transparent solution after ultrasonic treatment;

[0074] S3. Add 12.8 g of tetraethyl orthosilicate to the transparent solution obtained in step S2, and add 2 mol / L nitric acid dropwise to adjust the pH to about 9. While ultrasonically treating, slowly add the nano titanium dioxide dispersion obtained in step S1, ultrasonicate for 60 seconds, stir and hydrolyze at a shear rate of 300 r / min at 45°C for 24 hours. After the reaction is completed, separate the product from the reaction system by centrifugal separation, wash the product with ethanol for multiple times, dry the washed product at room temperature, and finally calcine at 550°C for 6 hours to obtain modified nano titanium dioxide.

[0075] 2. Preparation of PE film

[0076] 70 parts of linear low-density polyethylene 7042, 30 parts of metallocene linear low-density polyethylene D139, 1 part of anti-blocking agent erucic acid amide DY-014, 3 parts of modified nano-titanium dioxide obtained in step 1, 1 part of light shielding agent carbon black, 0.5 parts of nucleating agent sodium benzoate, and 5 parts of polyethylene filler masterbatch TC-313T are added into a twin-screw extruder, melt-mixed at a screw speed of 65 r / min, extruded when the hot melt temperature reaches 170°C, and then inflated, pulled, cooled, and rolled to obtain a PE film.

[0077] Example 2 Preparation of a modified nano-titanium dioxide and PE film

[0078] The difference from Example 1 is that in step S3, the mass of n-octylamine is changed from 2.50 g to 2.25 g, that is, the mass ratio of CTAB to n-octylamine is 1:1.8.

[0079] The other steps and conditions are the same as those in Example 1.

[0080] Example 3 Preparation of a modified nano titanium dioxide and PE film

[0081] The difference from Example 1 is that in step S3, the mass of n-octylamine is changed from 2.50 g to 2.75 g, that is, the mass ratio of CTAB to n-octylamine is 1:2.2.

[0082] The other steps and conditions are the same as those in Example 1.

[0083] Example 4 Preparation of a modified nano-titanium dioxide and PE film

[0084] The difference from Example 1 is that in step 2, the number of modified nano titanium dioxide is changed from 3 parts to 5 parts.

[0085] The other steps and conditions are the same as those in Example 1.

[0086] Example 5 Preparation of a modified nano-titanium dioxide and PE film

[0087] The difference from Example 1 is that in step 2, the number of light shielding agents is changed from 1 part to 3 parts.

[0088] The other steps and conditions are the same as those in Example 1.

[0089] Comparative Example 1 Preparation of a PE film

[0090] The difference from Example 1 is that in step 2, the modified nano titanium dioxide is replaced by an equal amount of nano titanium dioxide powder.

[0091] The other steps and conditions are the same as those in Example 1.

[0092] Comparative Example 2 Preparation of a modified nano titanium dioxide and PE film

[0093] The difference from Example 1 is that in step 2, no light shielding agent is added.

[0094] The other steps and conditions are the same as those in Example 1.

[0095] Comparative Example 3 Preparation of a modified nano titanium dioxide and PE film

[0096] The difference from Example 1 is that in step 2, no nucleating agent is added.

[0097] The other steps and conditions are the same as those in Example 1.

[0098] Comparative Example 4 Preparation of a modified nano titanium dioxide and PE film

[0099] The difference from Example 1 is that in step 2, no nucleating agent and light shielding agent are added.

[0100] The other steps and conditions are the same as those in Example 1.

[0101] Comparative Example 5 Preparation of a modified nano titanium dioxide and PE film

[0102] The difference from Example 1 is that in step 2, the light shielding agent carbon black is replaced by an equal amount of light shielding agent titanium dioxide.

[0103] The other steps and conditions are the same as those in Example 1.

[0104] Comparative Example 6 Preparation of a modified nano titanium dioxide and PE film

[0105] The difference from Example 1 is that in step 2, the light shielding agent carbon black is replaced by an equal amount of ultraviolet absorber UV-531.

[0106] Comparative Example 7 Preparation of a modified nano titanium dioxide and PE film

[0107] The difference from Example 1 is that in step S3, the mass of n-octylamine is changed from 2.25 g to 1.25 g, that is, the mass ratio of CTAB to n-octylamine is 1:1.

[0108] The other steps and conditions are the same as those in Example 1.

[0109] Comparative Example 8 Preparation of a modified nano-titanium dioxide and PE film

[0110] The difference from Example 1 is that in step S3, the mass of n-octylamine is changed from 2.25 g to 3.75 g, that is, the mass ratio of CTAB to n-octylamine is 1:3.

[0111] The other steps and conditions are the same as those in Example 1.

[0112] Comparative Example 9 Preparation of a modified nano-titanium dioxide and PE film

[0113] The difference from Example 1 is that in step 2, the number of modified nano titanium dioxide is changed from 3 parts to 2 parts.

[0114] The other steps and conditions are the same as those in Example 1.

[0115] Comparative Example 10 Preparation of a modified nano titanium dioxide and PE film

[0116] The difference from Example 1 is that in step 2, the number of modified nano titanium dioxide is changed from 3 parts to 6 parts.

[0117] The other steps and conditions are the same as those in Example 1.

[0118] Comparative Example 11 Preparation of a modified nano titanium dioxide and PE film

[0119] The difference from Example 1 is that in step 2, the amount of the light shielding agent is changed from 1 part to 0.5 parts.

[0120] The other steps and conditions are the same as those in Example 1.

[0121] Comparative Example 12 Preparation of a modified nano titanium dioxide and PE film

[0122] The difference from Example 1 is that in step 2, the number of light shielding agents is changed from 1 part to 4 parts.

[0123] The other steps and conditions are the same as those in Example 1.

[0124] Experimental example: Mechanical properties and degradation performance test of PE film

[0125] 1. Experimental Methods

[0126] (1) Elongation at break: The elongation at break of the film samples of each embodiment and comparative example before photodegradation was tested in accordance with GB / T 1040.3-2006 "Determination of tensile properties of plastics Part 3: Test conditions for films and sheets". In this application, the inventor is committed to developing innovative products with mechanical properties that significantly exceed industry standards. To achieve this goal, this application specifically sets strict mechanical performance indicators, among which the elongation at break is set to be greater than 400%, which is significantly higher than the industry standard (>100%), and this standard is used to judge whether the material has excellent mechanical properties.

[0127] (2) Weight loss rate: The PE film samples of each embodiment and comparative example were subjected to a photodegradation test, and the test standard was implemented in accordance with GB / T9344-1988 "Plastic Xenon Lamp Light Source Exposure Test Method". The xenon lamp was used for radiation, and the radiation power was 300W / m 2 , then the radiation dose per hour is 1.08MJ / m 2 The annual average total solar radiation in western Guangdong (45°) is 5400 MJ·m -2 , ultraviolet radiation accounts for 4%, and the total annual ultraviolet radiation is 216MJ·m -2. According to the amount of light radiation converted into the number of days for the induction period and the number of days required for the degradation period, the hourly radiation under the test conditions is equivalent to the ultraviolet radiation of 1.8 days of actual ambient light. The product design of this application is intended to: ensure that the weight loss rate caused by catalytic degradation is less than 20% within one year (i.e. 200h×1.8=360 days in this application), so that it can effectively protect the quality of the pipes and prevent the embrittlement of the PE film during the one-year storage period before the pipes leave the factory; after a storage period of more than one year, the weight loss rate of the product every 90 days (50h×1.8=90 days) is doubled compared to the weight loss rate within one year (200h×1.8=360 days), so as to achieve rapid and efficient natural degradation and meet environmental protection needs. The total radiation time of this test is 300h. The PE film samples before and after exposure are weighed every 50h to calculate the weight loss rate of the film.

[0128] 2. Experimental results

[0129] Table 1 Statistical table of weight loss and elongation at break of PE films of embodiments and comparative examples

[0130]

[0131]

[0132] It can be concluded from the data in Table 1 that in Examples 1 to 5, the modified nano-silicon dioxide used has a smaller mesopore diameter, which effectively reduces the specific surface area of ​​its contact with organic matter, thereby significantly reducing the degradation rate of the film. At the same time, the added light-shielding agent carbon black can not only effectively absorb ultraviolet visible light within the range of 400nm, but also has a unique quenching excited state function. When there is unabsorbed or reflected light penetrating into the film material, the modified nano-titanium dioxide in the material will generate hydroxyl radicals (·OH) with strong oxidizing properties on its surface under ultraviolet irradiation. At this time, the hydrogen atoms on the surface of carbon black can be transferred to these hydroxyl radicals and react with them, thereby effectively preventing these highly active substances from photo-oxidation reactions with organic matter adsorbed on the surface of modified nano-titanium dioxide particles. In addition, the addition of a nucleating agent effectively compensates for the problem of decreased film physical properties caused by the addition of light-shielding agent carbon black. Therefore, the PE film prepared by the present application effectively shields the light, and the photo-oxidation effect of the modified nano-titanium dioxide on organic matter is significantly weakened, thereby effectively inhibiting the photocatalytic degradation efficiency of the PE film, so that the obtained PE film has a suitable degradation efficiency, ensuring that the weight loss rate of the obtained PE film is less than 20% within one year (200h×1.8=360 days), and after a storage period of more than one year, the weight loss rate of the product every 90 days (50h×1.8=90 days) is doubled compared to the weight loss rate within one year, achieving rapid and efficient natural degradation, meeting the needs of environmental protection. At the same time, the film also has excellent mechanical properties (elongation at break>400%).

[0133] Compared with Example 1, since Comparative Example 1 does not use modified nano-titanium dioxide, the mesopore size cannot be adjusted, resulting in an excessively fast degradation rate, which leads to a rapid increase in the weight loss rate after 50 hours and cannot meet the protection period requirement of PVC pipe packaging.

[0134] Compared with Example 1, it can be seen that when Comparative Example 2 does not add light-shielding agent carbon black, the synergistic effect between the light-shielding agent and the modified nano-titanium dioxide cannot be exerted to slow down the degradation rate, resulting in a significantly higher weight loss rate within 200 hours than that of Example 1; in addition, although no light-shielding agent is added, the elongation at break of the film remains at a high level, because the lack of the light-shielding agent has little effect on the mechanical properties of the film; Comparative Example 3 lacks a nucleating agent, which greatly reduces the elongation at break performance of the film; Comparative Example 4 lacks both a light-shielding agent and a nucleating agent, so that the weight loss rate at 150 hours has exceeded 20%, and the degradation rate is too fast to meet the requirement of one-year storage of pipe packaging.

[0135] Compared with Example 1, Comparative Example 5 uses other types of light shielding agent titanium dioxide, which can only absorb and reflect ultraviolet rays with a wavelength range of ≤400nm, and does not have the function of quenching the excited state. Ultraviolet rays exceeding this range can pass through the film, which makes the weight loss rate of the film within 200h>20%, which cannot meet the requirements of pipe packaging; although Comparative Example 6 uses ultraviolet absorber UV-531, the absorber can only block part of the ultraviolet rays (240~340nm), and some ultraviolet rays still penetrate into the product, resulting in accelerated catalytic degradation rate. The weight loss rate within 200h is>30%, so it also fails to meet the performance requirements of pipe packaging that can effectively protect the pipe within one year.

[0136] Comparison of Examples 1 to 3 with Comparative Examples 7 to 8 shows that the molar ratio of CTAB to n-octylamine has a significant effect on the degradation rate of the film. In Comparative Example 7, n-octylamine is too little, resulting in a too fast weight loss rate of the film in 150 to 200 hours, and a too slow growth of the degradation rate over 200 hours; in Comparative Example 8, due to an excess of n-octylamine, the weight loss rate of the film in 300 hours is too small (<40%), both of which do not meet the requirements.

[0137] By comparing Example 1 and Example 4 with Comparative Examples 9 to 10, it can be seen that when the addition amount of modified nano titanium dioxide is 3 to 5 parts, the weight loss rate of the film changes little within 200 hours, and the weight loss rate changes greatly after more than 200 hours, which not only meets the requirements of pipe packaging, but also meets the requirements of rapid degradation of PE film after one year; the addition amount of modified nano titanium dioxide lower than (Comparative Example 9) or higher than this range (Comparative Example 10) does not meet the performance requirements of weight loss rate change.

[0138] By comparing Example 1 and Example 5 with Comparative Examples 11 to 12, it can be seen that when the added amount of light shielding agent is 1 to 3 parts, the weight loss rate of the PE film within 200 hours is small, and it also meets the environmental protection requirements after more than 200 hours; when the added amount of light shielding agent is lower than (Comparative Example 11) or higher than this range (Comparative Example 12), the weight loss rate change will not meet the requirements.

[0139] In summary, the present invention obtains modified nano titanium dioxide by adding hexadecyltrimethylammonium bromide and n-octylamine. Subsequently, it is combined with low-density polyethylene, filler, light shielding agent, nucleating agent and opening agent to prepare a PE film. Among them, the smaller mesopore diameter of the modified nano titanium dioxide reduces its contact area with organic matter, thereby reducing the degradation rate of the film; the light shielding agent carbon black can not only absorb and reflect ultraviolet rays, but also quench free radicals on the surface of nano titanium dioxide, synergistically weakening the photocatalytic degradation effect; at the same time, the nucleating agent effectively compensates for the problem of decreased physical properties of the film caused by the addition of the light shielding agent. The synergistic effect of the above raw materials ensures that the PE film can effectively protect the pipe during the storage period, and can be quickly degraded after the storage period, and maintains excellent mechanical properties.

[0140] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A modified nano titanium dioxide, characterized in that: The raw materials include: nano titanium dioxide, hexadecyltrimethylammonium bromide, n-octylamine, silicon source; Wherein, the molar ratio of hexadecyltrimethylammonium bromide to n-octylamine is 1:(1.8-2.2).

2. The modified nano titanium dioxide according to claim 1, characterized in that: The nano titanium dioxide is anatase nano titanium dioxide and / or rutile nano titanium dioxide.

3. The modified nano titanium dioxide according to claim 1, characterized in that: The silicon source includes one or more of tetraethyl orthosilicate, silicate, and silane.

4. The method for preparing the modified nano titanium dioxide according to any one of claims 1 to 3, comprising the following steps: S1. The hexadecyl trimethyl ammonium bromide and n-octylamine were thoroughly mixed to obtain a transparent solution; S2. Add a silicon source to the transparent solution obtained in step S1, adjust the pH to 9 to 11, mix thoroughly, then add the nano-titanium dioxide dispersion, heat to 40 to 50 ° C, react fully, and post-treat to obtain a precursor; S3. The precursor obtained in step S2 is heated to 500-600° C. and calcined to obtain modified nano titanium dioxide.

5. A PE film, characterized in that: By weight, it includes the following components: 60-80 parts of linear low-density polyethylene; 20-40 parts of metallocene linear low density polyethylene; 5-10 parts of filler; 3 to 5 parts of the modified nano titanium dioxide according to any one of claims 1 to 3; 1-3 parts of carbon black; 1 to 3 parts of opening agent; Nucleating agent 0.5 to 1 part.

6. The PE film according to claim 5, characterized in that: The nucleating agent includes one or more of sodium benzoate, benzoic acid, and 1,3:2,4-di-p-methylbenzylidene sorbitol.

7. The PE film according to claim 5, characterized in that: The opening agent includes one or more of silicon dioxide, oleamide, and erucamide.

8. The preparation method according to claim 4, characterized in that: In step S2, the method for preparing the nano titanium dioxide dispersion comprises the following steps: The nano-titanium dioxide is fully dispersed in the solvent to obtain a nano-titanium dioxide dispersion.

9. The method for preparing a PE film according to any one of claims 5 to 7, characterized in that: The following steps are involved: All raw materials are fully mixed according to proportion, heated to 160-175°C, extruded, and post-treated to obtain PE film.

10. Use of the modified nano titanium dioxide according to any one of claims 1 to 3 or the PE film according to any one of claims 5 to 7 in the preparation of tube packaging.

Citation Information

Patent Citations

  • Porous silicon dioxide-coated titanium dioxide nanopowder photocatalytic material and preparation method thereof

    CN107008242A

  • Heat-resistant and low-temperature-resistant PE film and preparation process thereof

    CN112250936A

  • Preparation method and application of anti-ultraviolet dendritic silicon dioxide nanomaterial

    CN113735129A